Pengaruh Kecerdasan Emotional Terhadap Kinerja Karyawan PT. Mopoli Raya Kecamatan Pematang Jaya - Syardiansah Syardiansah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
This research was conducted to determine the effect of emotional intelligence on the performance of employees of PT Mopoli Raya, Pematang Jaya District. The population in this study were 345 employees. Using the Slovin formula, the number of respondents taken was 78 employees. The data in this study were obtained from the results of distributing questionnaires to 78 employees in the workplace of PT Mopoli Raya, Pematang Jaya District. From the results of data analysis, it was found that the value of t sig. emotional intelligence variable of 0.077 compared with alpha of 0.05, there is no significant effect of emotional intelligence on the performance of employees of PT Mopoli Raya, Pematang Jaya District. The results of testing the coefficient of determination obtained that the coefficient of determination (R) variable emotional intelligence of 0.009. This means that the independent variable only has an effect of 0.9% on the dependent variable.